ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI TERAPI PIJAT OKETANI UNTUK MENINGKATKAN PRODUKSI DAN EJEKSI ASI PADA IBU POSTPARTUM ANEMIA DI RUMAH SAKIT BHAYANGKARA TINGKAT I RADEN SAID SUKANTO JAKARTA TIMUR - Dwi Arini (2022)
Postpartum mothers face the problem of breast milk incontinence, which requires innovative non-pharmacological therapeutic interventions for oketani massage. Oketani massage therapy is a therapy to overcome lactation problems such as insufficient milk production, full breasts, and ineffective milk supply. Oketani massage will make the breasts become soft and the areola becomes more flexible, the productive ducts and areola also become elastic. The whole breast becomes more elastic and produces high quality breast milk due to its total solid content, fat binding and increased energy. Oketani massage therapy is done in 3 days every morning and evening with a time of 30 minutes. This writing aims to monitor care with the intervention of oketani massage innovation on breastfeeding care for postpartum mothers at Bhayangkara Hospital Level I Raden Said Sukanto, East Jakarta. This case study involved the intervention and control groups, which included nursing care and interventional treatment of oketani massage as the intervention group and the control group only received care during treatment without getting oketani massage. Analysis of follow-up nursing care with oketani massage intervention got significant results from postpartum mother's milk compared to respondents who did not get oketani massage intervention. It is hoped that this case study can provide information for health services regarding the provision of oketani massage therapy to breastfeed postpartum mothers.